Tetra-amido macrocyclic ligand (TAML) at silicon(IV): a structurally constrained, water-soluble silicon lewis superacid - Hannibal, Valentin D.; Greb, Lutz (Journal of the American Chemical Society, 2024)
Tetracoordinate silicon species are typically tetrahedral, weak Lewis acids, and often sensitive to moisture. In this study, we present a tetra-amido macrocyclic ligand (TAML)-substituted Si(IV), isolated as its bis(pyridine) adduct. Due to structural constraint toward anti van’t-Hof/Le Bel geometry, this compound exhibits Lewis superacidity and effectively catalyzes the hydroboration of pyridine. Kinetic and computational analyses of the catalytic cycle reveal that TAML-Si(IV) acts as a hydride transfer agent, and the hydrido silicate key intermediate is isolated. Notably, the Lewis acid is highly soluble (5 g/L) and long-term stable in water. Unlike previously described silicon-H2O adducts, the bound water becomes substantially acidified, reaching the Bro̷nsted superacidity range. A comparison of water affinity versus pKa lowering confirms our previous theory of the strength and the effect of Lewis acids. Overall, the compound’s unlimited water compatibility and its mechanistically understood catalytic efficiency mark significant progress in applying structural constraint strategies for p-block element-based catalysis, while the acidification touches critical aspects of zeolite and silica surface chemistry.
Gesehen am 07.02.2025